Pelaksanaan Pemenuhan HAK Warga Binaan Wanita di Rumah Tahanan Kelas IIB Serang - Devi Febiola Setiawaty; Rokilah Rokilah; Hasuri Hasuri (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2024)
Ensuring the rights of all inmates, particularly women, is an essential obligation of basic human rights. Even during their temporary stay at Serang Detention Center for treatment and training, their rights must be upheld. The center not only provides maintenance assistance but also training for women. It is essential to adhere to the Corrections Law Number 22 of 2022 and Government Regulation Number 32 of 1999 and other related regulations to offer guidance and care in accordance with their rights. Women have distinct privileges from men, and it is crucial to recognize and provide accordingly. This research aims to explore how to uphold the rights of women inmates at Class IIB Serang Detention Center using empirical juridical research. The research sources include primary data obtained through direct interviews and secondary data from laws, books, journals, theses, and tertiary materials such as relevant websites. The research results indicate that the center offers paid training, including spiritual training, physical training, and independence training, that include the right to worship and celebrate religious holidays, maintain good health, and other rights regulated by law. However, there are challenges in providing these rights, such as a lack of self-reliance programs, insufficient accommodation for spiritual training for religions other than Islam and Christianity, and overcapacity concerns at Serang Detention Center.